(untitled) (Homoeopathy for All, 2026)
In today’s interconnected world, the meaning of Swadeshi must evolve beyond its narrow interpretation of geographical origin. In its true contemporary sense, Swadeshi is not merely about where an idea was born—it is about where it has taken root, where it has grown, and whom it serves. Swadeshi, today, must be defined by: • Value creation within the nation • Indigenous capacity-building • Contribution to public welfare • Integration into national systems • Acceptance by the people By this evolved definition, India has already embraced a pragmatic Swadeshi philosophy in multiple sectors.